TECHNICAL APPLICATION OF DENOISING KALMAN FILTER FOR ARTIFACT REDUCTION IN MRI ANATOMIC IMAGE INFORMATION - Puspitaningtyas, Dyah Ayu; Mulyantoro, Donny Kristanto; Sudiyono, Sudiyono (Postgraduate Program , Poltekkes Kemenkes Semarang, 2021)
Fatsups and BLADE sequences are used to reduce artifacts and clarify anatomical images. Basedon theoretical studies, the STIR, BLADE sequences, the addition or subtraction of parameters, and theaddition of artificial intelligence used still have a weakness, namely increasing the scanning time to belonger. Another technique that can be used and sequences and parameters on MRI is the denoisingKalman filter technique in the Matlab (Matrix Laboratory) program. The denoising technique is appliedafter the scanning process. Denoising will not increase the MRI scanning time. This systematic reviewaims to know the technical application of denoising Kalman filter for reduction artifacts on MRIexamination. The search was done using google scholar, WILEY, IEE Explore, SPRINGER,PERPUSNAS, and Scopus in English with 2004-2020 articles period. The keywords are MRI artifact,reducing artifacts, and the Kalman filter algorithm. A review of 4 articles of filter Kalman intervention onMRI Brain, MRI Abdomen, and MR Cardiac shows that the Kalman filter is good enough to reduceartifacts and improve anatomical information. The Kallman filter could reduce flow artifacts, improveimage quality and clarify anatomical images on MRI.